Over sea, under stone [compact disc, unabridged] - Cooper, Susan, 1935- (Cooper, Susan, 1935- Dark is rising sequence, 2001)
Three children on vacation in Cornwall find an ancient manuscript which sends them on a dangerous quest that entraps them in the eternal battle between the forces of the Light and the Dark.